Significant correlation of ischemic stroke with peripheral artery disease in type 2 diabetes mellitus patients - Gupta, Vishal Kumar; Gupta, Ajesh Chandra; Giri, Richa; Palawat, Sandeep Singh (International Journal of Advances in Medicine, 2022)
Background: Atherosclerotic disease is not only increased in incidence in type 2 diabetic patients, but its course is also accelerated. Stroke is one of the major causes of morbidity and mortality among the elderly population. The relationship between ischemic stroke and PAD (peripheral artery disease) has been poorly investigated in India. So, we studied the risk of stroke in PAD patients with type 2 diabetes. The aims and objectives of the study were to study the prevalence of PAD in patients with type 2 diabetes mellitus and to study the correlation of stroke in PAD patients with type 2 diabetes. Methods: Hospital based cross-sectional study was conducted among the 124 patients admitted with type 2 diabetes (age >25 years) from December 2019 to October 2021 in the various units of department of medicine/surgery, KPS institute, GSVM medical college, Kanpur. Color Doppler of limbs and carotid artery was done in study population. Clinical sign and symptoms, history of stroke or diagnostic investigation were used for evaluate cerebrovascular events. Results: In our study based on doppler ultrasound, the prevalence of PAD was found in 31 patients (25%) out of 124 with men having a higher prevalence (24 out of 74; 77.4%), as compared to women (7 out of 50; 22.6%) (p=0.020). The prevalence of stroke was 32.3% in PAD patients and 11.8% in non-PAD patients (p=0.009). Conclusions: By using Doppler, we found evidence of PAD in 25% of type 2 diabetics (M>F). The prevalence of stroke was 32.3% in PAD patients and 11.8% in non-PAD patients (p=0.009). PAD is associated with an increased risk of cerebrovascular disease morbidity and mortality. Clinician should identify a PAD patient with diabetes to elicit symptoms, complications like stroke to decrease mortality or morbidity.